2017
DOI: 10.2134/jeq2016.09.0379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing Management and Buffer Strips on Metal Runoff from Pastures Fertilized with Poultry Litter

Abstract: Metal runoff from fields fertilized with poultry litter may pose a threat to aquatic systems. Buffer strips located adjacent to fields may reduce nutrients and solids in runoff. However, scant information exists on the long-term effects of buffer strips combined with grazing management on metal runoff from pastures. The objective of this study was to assess the 12-yr impact of grazing management and buffer strips on metal runoff from pastures receiving poultry litter. The research was conducted using 15 waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Therefore, the main objective of this paper was to evaluate the long‐term effects of grazing management strategies and buffer strips on P loads and concentrations in runoff from pastures fertilized with poultry litter. Earlier research on the watersheds in this study showed that grazing management practices in combination with buffer strips can significantly reduce soil erosion (Pilon, Moore, Pote, Pennington, et al., ), metal runoff (Pilon, Moore, Pote, Martin, & DeLaune, 2017a), and N runoff (Pilon et al., ).…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Therefore, the main objective of this paper was to evaluate the long‐term effects of grazing management strategies and buffer strips on P loads and concentrations in runoff from pastures fertilized with poultry litter. Earlier research on the watersheds in this study showed that grazing management practices in combination with buffer strips can significantly reduce soil erosion (Pilon, Moore, Pote, Pennington, et al., ), metal runoff (Pilon, Moore, Pote, Martin, & DeLaune, 2017a), and N runoff (Pilon et al., ).…”
Section: Introductionmentioning
confidence: 56%
“…Pilon, Moore, Pote, Pennington, et al (2017) observed lower bulk density in hayed pastures compared with continuously grazed pastures. Moreover, results from the same research showed higher runoff volumes and sediment loads in pastures that were continuously grazed over 12 yr compared with hayed pastures (Pilon, Moore, Pote, Martin, & DeLaune, 2017). A grazing study conducted by Hann et al (2003) showed greater concentrations and loads of TP in runoff from pastures that were grazed compared with ungrazed or hay systems.…”
mentioning
confidence: 89%
See 3 more Smart Citations